Agricultural cooperatives as social capital hubs – A case in a post-socialist country. Issue 1 (June 2021) - Tuna, Emelj; Karantininis, Kostas
Highlights: Social Network analysis and social capital structures in post-social countries. Evidence that the members of agricultural cooperatives have better access to information and resources. Cooperative managers have essential role in information diffusion and confidence boost among cooperative members. Identifying powerful individuals - constructing cooperation models in which these powerful individuals can have valuable role in information diffusion. Positive example for small-scale farmers still doubting the concept of cooperation. Abstract: Agricultural cooperatives in post-socialistic countries often fail to justify their purpose. Lack of trust and social capital are plausible reasons. In this paper we map the relationship structure of farmers that seek information about rural development programs, in a region where cooperatives operate. The Social network analysis demonstrates low levels of social capital, however, the cooperative acts as valuable information provider for its members, serving as information mediator to the rural development program's resources, required for farmers' investment initiatives. This is a positive evidence of small-scale farmers' attitudes towards cooperatives and a step forward towards cooperation and re-establishment of agricultural cooperatives in post-socialist countries.